Consolidation of a collar truss with a steel cable system - Crivellari, Giacomo (2016)
Post-tensioning techniques for strengthening existing timber elements have been used throughout history with excellent results. Former applications on wooden trusses have already shown some of the advantages of such a consolidating system, but very few tests were performed on the topic. During an experimental campaign, a full-scale historical timber truss was deeply analysed and tested in its original (unreinforced) condition, reaching a considerable level of damage. It was later repaired with a steel cable system, using prestresses to recover the structure bearing capacity, and tested again. The results show that the repair allowed a recovery of at least the 80% of the ultimate load-carrying capacity. The complete failure was not achieved, but it is likely to be presumed that the structure could have regained the totality of its strength. The data acquired in both tests were later compared in order to understand in detail the behavior of the truss.